The Peran Pasar Lokal Kampung Osing Dalam Meningkatkan Perekonomian Dan Budaya Desa Kemiren (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia is a country that has various cultures and each region definitely has a different culture. Preserving culture in the modern era can be done in various ways, one of which is by creating a traditional market such as the Kampung Osing Local Market in Kemiren Village, Banyuwangi Regency. This research aims to explore more deeply the role of the Osing Village Local Market in improving the economy and culture of Kemiren Village. This research uses qualitative research methods with an ethnographic approach and research data sources are obtained through observation, documentation and interviews. The research results show that the Osing Village Local Market exists to increase the selling price of typical Osing Tribe snacks and to introduce the uniqueness of the Osing Tribe to local and international tourists. The presence of Lesung and Jaranan music performances as well as traders wearing traditional Osing tribe clothing are the main attractions in attracting tourists. The assistance that has been provided has made the Kampung Osing Local Market better and more attractive. The Osing Village Local Market plays a big role in improving the community's economy and the economy of Kemiren Village. Apart from that, with this market, the culture of the Osing Tribe is also increasingly known to the wider community. Innovations are still being carried out by the Osing Village Local Market committee so that the market remains sustainable and sustainable.